Pre-Trial in the Criminal Justice System in Military Criminal Judges in Indonesia - Sugeng Sutrisno (International Journal of Business and Social Science Research, 2021)
Law enforcement in the Military Court System in the settlement of criminal cases committed by TNI soldiers is seen as not yet fully guaranteeing legal protection for the rights of suspects, this is due to the absence of a control agency that oversees the actions of law enforcement officers in carrying out their duties and authorities as is the case in the system. General Court. This condition should not drag on indefinitely, because it will affect the law enforcement process and harm the suspect to fight for his rights to obtain justice which results in human rights violations (TNI soldiers). The purpose of the establishment of the Pretrial Institution is as stated in the Elucidation of Article 80 of the Criminal Procedure Code which states that this article intends to uphold law, justice, and truth through horizontal supervision. Settlement of criminal cases in Indonesia in addition to the Code of Criminal Procedure Code (KUHAP) which applies to civil society, we also recognize the existence of the Military Criminal Procedure Code which is regulated in Law Number 31 of 1997 concerning Military Courts, namely the law that regulates the procedure for resolving criminal cases. a criminal case committed by a TNI soldier. The Law on Military Courts includes the provisions of the litigation process (Military Criminal Procedure Law) starting from the investigation stage, submission of cases, the examination process at trial to the implementation of decisions. 31 of 1997 does not regulate pretrial. In several cases in the Military Court where a suspect was detained without a warrant for detention or was late in obtaining a warrant for detention, therefore such actions may conflict with the principles applicable in the provisions of criminal law so that they do not respect the position of the suspect as a creature created by God, even the act can lead to human rights violators. Therefore, in the military justice system in Indonesia, pretrial institutions are needed as a form of horizontal external supervision.